Nose and lungs: one way, one disease - Caimmi Davide; Marseglia Alessia; Pieri Giovanni; Benzo Serena; Bosa Luca; Caimmi Silvia (BMC, 2012)
Abstract It's well established that asthma, allergic rhinitis and rhinosinusitis are three closely related disease. In pediatrics, these conditions represent a common issue in daily practice. The scientific community has recently started to simply evaluate them as different manifestations of a common pathogenic phenomenon. This consideration relates to important implications in the clinical management of these diseases, which may affect the daily activity of a pediatrician. The unity of the respiratory tract is confirmed both from a morphological and from a functional point of view. When treating rhinitis, it is often necessary to assess the presence of asthma. Patients with sinusitis should be evaluated for a possible concomitant asthma. Conversely, patients with asthma should always be evaluated for possible nasal disease, especially those suffering from difficult-to-treat asthma, in which an occult sinusitis may be detected. The medications that treat nasal diseases appear to be useful in improving asthma control and in reducing bronchial hyperresponsiveness. It seems therefore important to analyze the link between asthma and sinusitis, both in terms of clinical and pathogenic features, as well the therapeutic approach of those patients presenting with these diseases.